PENYULUHAN DAN PEMERIKSAAN KADAR HEMOGLOBIN DENGAN METODE POCT (POINT OF CARE TESTING) SEBAGAI UPAYA PENCEGAHAN ANEMIA BAGI MASYARAKAT DI RT 03 RW 06 KELURAHAN TLOGOMAS KECAMATAN LOWOKWARU KOTA MALANG: COUNSELING AND EXAMINATION OF HEMOGLOBIN LEVELS USING THE POCT (POINT OF CARE TESTING) METHOD AS AN EFFORT TO PREVENT ANEMIA FOR THE COMMUNITY - Ummah*, Wiqodatul; Kuswandari, Eti; Utami, Woro Tri (JAMAS : Jurnal Abdi Masyarakat, 2024)
Cases of anemia in Indonesia are still quite high. The results show that the national prevalence rate of anemia in all age groups is 21.70%. While the prevalence of anemia in East Java Province is 5.8%. Anemia is a condition of decreased hemoglobin, hematocrit, and red blood cell counts below normal values. This condition is commonly referred to as blood deficiency. Anemia can be detected by measuring hemoglobin (Hb) levels using the POCT (Point of Care Testing) method. The Point of Care Testing (POCT) method according to the College of American Pathologists is an examination performed outside the laboratory location, using equipment that can be brought close to the patient to get immediate results. The purpose of this activity is as a form of Higher Education Dharma in the field of Community Service Wira Husada Nusantara Malang Health Polytechnic and as a place to apply Midwifery knowledge. Based on the background above, the authors are interested in doing community service free Hb checks and outreach about anemia in the community at RT 03 RW 06 Tlogomas Village, Lowokwaru District, Malang City. Participants who took part in this activity as many people. The conclusions from counseling and examining hemoglobin levels using the POCT (Point of Care Testing) method as an effort to prevent anemia for the community in RT 03 RW 06 Tlogomas Village, Lowokwaru District, Malang City are 17 people experiencing mild anemia, and most people do not understand anemia.